Penerapan Metode Therapeutic Community di LRPPN Bhayangkara Indonesia Kota Medan - Laila Putri; Dea Adinda; Aisya Maharani; Michelle Simangunsong; M. Hazel Arrazeq (Yayasan Literasi Sains Indonesia, 2023)
The increase of drug abuse in Indonesia over the years has been costly, both to individuals and to society. One effort that can be made to free drug users from addiction is rehabilitation. The purpose of this devotion is to know the social work methods that are used at Lembaga Rehabilitasi Pencegahan Penyalahgunaan Narkotika Bhayangkara Indonesia Kota Medan. The method of this devotion is a descriptive qualitative with data collection techniques through observation and in-depth interviews with social worker and addiction counselor that are working at Lembaga Rehabilitasi Pencegahan Penyalahgunaan Narkotika Bhayangkara Indonesia Kota Medan. The results of the study indicate that a standard of social work adopted at Lembaga Rehabilitasi Pencegahan Penyalahgunaan Narkotika Bhayangkara Indonesia Kota Medan is a nine-month therapeutic community method focused on psychosocial changes. Therapeutic community is a joint treatment performed between former drug users by living in one environment and thus helping one another to achieve healing.